Investigating the drivers of firm internationalisation: A fuzzy set analysis using Global Entrepreneurship Development Index data - Takawira Munyaradzi Ndofirepi (Economies, 2024)
Firm internationalisation, a key driver of global economic growth, is influenced by various entrepreneurial resources. This study explores the relationships between human capital, risk capital, risk acceptance, opportunity perception, and firm internationalisation using cross-national data from the Global Entrepreneurship Development Index (GEDI). Employing fuzzy set qualitative comparative analysis (fsQCA), this study analyzes data from 137 countries. The findings highlight two primary configurations driving internationalisation: (1) risk acceptance and opportunity perception, and (2) risk capital and opportunity perception. Opportunity perception emerges as a critical factor in both configurations, while human capital is not found to be a necessary condition. These results contribute to a better understanding of the factors that foster firm internationalisation and inform policies aimed at promoting global entrepreneurial ecosystems.
Keywords: 330; entrepreneurship; firm internationalisation; fsQCA; GEDI; opportunity perception; risk acceptance